Exploring students' perspectives of artificial intelligence's roles in language learning: analysis between IIUM and UNIRAZAK - Wan Yusof, Wan Putri Zaharah; Abdul Halim, Shamilah; Mohd Radzi, Khadijah (Faculty of Languages and Communication, UniSZA, 2024)
The rapid emergence of Artificial Intelligence (AI) technologies in education is beyond expectations. Many lecturers and students use AI tools such as ChatGPT, Chatbot, and Grammarly to teach and learn. As AI offers potential transformation to the education setting, it is important to understand students' experiences and attitudes towards the effectiveness of integrating AI tools in their language learning (Adiguzel et al., 2023; De la Vall et al., 2023; Sol et al., 2024). This study aims to explore perspectives and attitudes between International Islamic University Malaysia (IIUM) and Universiti Tun Abdul Razak (UNIRAZAK) students on Artificial Intelligence (AI) 's roles in language learning. The study uses a qualitative methodology through a series of in-depth interviews with language students at IIUM and UNIRAZAK in Kuala Lumpur. Three participants from each campus were chosen for this study. The results indicate that students valued the AI's efficiency and communication response towards their learning more than those who were concerned about the artificial human touch AI has to offer. Students reported various experiences when they used AI tools to complete their language projects, specifically in lexical items and grammatical structures. A few highlighted the need to enhance AI tools to assist their language learning further. Therefore, by highlighting the experiences and attitudes of students in AI-assisted language learning, the paper implies its endless potential in a supportive learning setting.